2022
DOI: 10.1021/jacs.1c13616
|View full text |Cite
|
Sign up to set email alerts
|

Noble-Metal High-Entropy-Alloy Nanoparticles: Atomic-Level Insight into the Electronic Structure

Abstract: The compositional space of high-entropy-alloy nanoparticles (HEA NPs) significantly expands the diversity of the materials library. Every atom in HEA NPs has a different elemental coordination environment, which requires knowledge of the local electronic structure at an atomic level. However, such structure has not been disclosed experimentally or theoretically. We synthesized HEA NPs composed of all eight noble-metal-group elements (NM-HEA) for the first time. Their electronic structure was revealed by hard X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
145
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(159 citation statements)
references
References 29 publications
1
145
0
Order By: Relevance
“…Table 4. Field lattice parameters obtained by XRD analysis and calculated analysis (Vegard's law) [13].…”
Section: Xrd Analysis Of the Cast Ccna Alloymentioning
confidence: 99%
See 1 more Smart Citation
“…Table 4. Field lattice parameters obtained by XRD analysis and calculated analysis (Vegard's law) [13].…”
Section: Xrd Analysis Of the Cast Ccna Alloymentioning
confidence: 99%
“…Previous research in the field of noble HEAs represents relatively new findings in the field of science. Only a couple of scientific papers [ 13 , 14 , 15 , 16 ] have been observed in the literature, which mainly deal with a single—phase PdPtRhIrCuNi type of alloy. In these papers, the rules for the formation of the SS phase [ 16 ], the development of nanoparticles of this type [ 13 ], the assumptions of mechanical properties [ 15 ], as well as the electrocatalytic use [ 17 ], are presented.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–6 ] The use of multiple elements significantly broadens the compositional space and affords tunable microstructures to achieve high performance. It is reported that HEA catalysts are featured with complex atomic configurations and diverse adsorption sites, which result in a near‐continuous distribution in binding energy [ 7–9 ] that is well‐suited for multi‐step reactions having a wide range of intermediates. [ 10 ] Meanwhile, the high‐entropy structure usually leads to the excellent structural stability of HEA catalysts, either through the thermodynamic entropy stabilization effect or kinetic sluggish diffusion, [ 11–20 ] thus promoting their applications in harsh environments.…”
Section: Introductionmentioning
confidence: 99%
“…High-entropy alloys (HEAs) and complex solid solutions hold great potential for catalyst discovery [1][2][3][4][5][6][7] because the metal surfaces can be tuned to maximize the likelihood of ideal binding sites for specific reactions in accordance with the Sabatier principle [8]. However, the huge composition space available to these materials presents a challenge to any rational discovery procedure, as the selection of constituent elements and ratios makes experimental screening virtually impossible.…”
Section: Introductionmentioning
confidence: 99%